2020
DOI: 10.2147/prbm.s241192
|View full text |Cite
|
Sign up to set email alerts
|

<p>Quality of Life and Emotional States of Depression, Anxiety and Stress in Adolescents with Polycystic Ovary Syndrome: A Cross-Sectional Study</p>

Abstract: Background: The chronic condition of polycystic ovary syndrome (PCOS) in adolescents can affect different aspects of quality of life in them. This study aimed to determine the correlation between the quality of life with emotional states of depression, anxiety, and stress in adolescents with PCOS. Methods: This is a cross-sectional study conducted on 120 adolescents with PCOS in Tehran, Iran in 2019. The sociodemographic checklist, quality of life, depression, anxiety and stress (DASS) were assayed by valid an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 41 publications
3
16
0
Order By: Relevance
“…27 One crosssectional study including 120 participants reported that QoL in adolescent girls with PCOS was moderately reduced, as outlined by the questionnaire scoring classification. 26 Meanwhile Trent et al 24,25 showed in two cross-sectional studies that QoL was reduced in adolescent girls with PCOS and these studies included a large number of adolescent girls with PCOS (n = 97). Adolescent girls with PCOS each scored lower in all domains of healthrelated QoL assessments when compared to healthy adolescent girls of a similar age range.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…27 One crosssectional study including 120 participants reported that QoL in adolescent girls with PCOS was moderately reduced, as outlined by the questionnaire scoring classification. 26 Meanwhile Trent et al 24,25 showed in two cross-sectional studies that QoL was reduced in adolescent girls with PCOS and these studies included a large number of adolescent girls with PCOS (n = 97). Adolescent girls with PCOS each scored lower in all domains of healthrelated QoL assessments when compared to healthy adolescent girls of a similar age range.…”
Section: Resultsmentioning
confidence: 99%
“…In all studies, adolescent girls completed the QoL questionnaires. Studies used different criteria for the diagnosis of PCOS and all but one study 26 did not report the age of menarche, which is an important factor to define menstrual irregularity in adolescents. The study characteristics are outlined in Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Murshid's (2017) investigation of the association between social support networks, as measured by parental involvement and close friendships, and depression among adolescents in South Asia demonstrated that social support was a social determinant of adolescent mental health. Stronger social support can result in children experiencing less anxiety, behavioral problems, and depressive symptoms (Alsubaie et al 2019;Saei Ghare Naz et al 2020). On the other hand, less social support negatively affects the levels of resilience, which is important in preventing depressive symptoms.…”
Section: Theoretical Backgroundmentioning
confidence: 99%